Effects of Muse Cell on a Mouse Model With Acute Encephalopathy - Tatsuya Kawaguchi; Tetsuji Mori; Kaori Adachi; Jun Fujii; Yoshihiro Maegaki; Fumiko Obata (Brain and Behavior)
ABSTRACT Introduction Acute encephalopathy (AE) in childhood due to a viral infection causes convulsions and altered consciousness, leading to severe sequelae and death. Among the four types of AE, cytokine storm–induced AE is the most severe and causes serious damage to the brain. Moreover, a fundamental treatment for AE has not been established yet. Recently, it has been shown that the administration of multilineage‐differentiating stress‐enduring (Muse) cells, a population of mesenchymal stem cells, improves symptoms in various types of brain injuries when administered in the subacute phase (1–7 days after brain damage). We aimed to examine the effects of Muse cells in a cytokine storm–induced AE animal model using immunocompromised nonobese diabetic/severe combined immunodeficiency (NOD/SCID) neonatal mice. Methods We established a modified protocol to induce AE‐like symptoms in NOD/SCID. Then, Muse cells were injected at an acute phase (2–4 h after hyperthermia treatment). Results Injection of Muse cells significantly improved body weight gain 1 day after treatment and the survival ratio for 3 weeks. Conclusion These effects could be a result of the direct and/or indirect upregulation of IL‐10, an anti‐inflammatory cytokine, in the Muse cell–treated brain. Although non‐Muse cells, a residual cell population in the bone marrow after isolating Muse cells, also improved some symptoms, their effects were weaker than those of Muse cells. Our results indicate that the injection of Muse cells in the acute phase has an effect on AE, suggesting that they exert their therapeutic effects not only in the subacute phase but also in the acute phase.